Problems of cost accounting for production and costs grouping (Journal of Economic Research & Business Administration, 2017)
Article is devoted to cost accounting problems on production and groups of costs. In article are consideredin a survey type of classification of costs and group of costs in an interpretation of various authors.Aspects of concepts of the cost accounting and calculation of products constantly costs in the agenda ofdiscussions of scientists and practicing. Moreover and in practice this problem is important, especially in theconditions of development of modern business. The necessity of classification of production costs is causedby cost management tasks in the companies with identification of objects, the existing cost groups and processesof their forming. Classification of costs shall answer the main task – to be based on the signs allowingto differentiate costs for management of them for the purpose of minimization of costs per unit of products.